2011
DOI: 10.1055/s-0031-1271708
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Fetal Diuresis with Intraamniotic Furosemide Injection Reduces Intestinal Damage in a Rat Model of Gastroschisis

Abstract: Intraamniotic furosemide injection caused a substantial decrease in ID encountered in gastroschisis. The induction of fetal diuresis with intraamniotic furosemide injection seems promising as a prenatal treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
4
0
2
Order By: Relevance
“…Goncalves et al 81 demonstrated reduced bowel thickness when administering a nitric oxide donor S‐nitrosoglutathione through a patch covering of the exposed bowel. Similar results have been found with the administration of maternal intraperitoneal cannabidiol, 80 transplacental dexamethasone, 84 intra‐amniotic furosemide injection to induce fetal diuresis 82 and the use of hydrogel with a fibrin adhesive 83 . Finally, amnioinfusion/amnioexchange also aims to reduce intra‐amniotic inflammation and has been shown to significantly improve bowel morphology in the sheep model 61 but not in the rabbit model 86…”
Section: Fetal Interventionssupporting
confidence: 60%
See 1 more Smart Citation
“…Goncalves et al 81 demonstrated reduced bowel thickness when administering a nitric oxide donor S‐nitrosoglutathione through a patch covering of the exposed bowel. Similar results have been found with the administration of maternal intraperitoneal cannabidiol, 80 transplacental dexamethasone, 84 intra‐amniotic furosemide injection to induce fetal diuresis 82 and the use of hydrogel with a fibrin adhesive 83 . Finally, amnioinfusion/amnioexchange also aims to reduce intra‐amniotic inflammation and has been shown to significantly improve bowel morphology in the sheep model 61 but not in the rabbit model 86…”
Section: Fetal Interventionssupporting
confidence: 60%
“…Animal studies have also investigated the potential effects of direct and indirect introduction of anti‐inflammatory agents into the amniotic cavity to mitigate amniotoxicity 80‐86,94 . Nitric oxide levels are elevated in AF of fetuses with gastroschisis, producing a negative feedback effect on the bowels thereby diminishing its important physiologic role in developing mucosal permeability, muscle motility, wound healing and vasodilation.…”
Section: Fetal Interventionsmentioning
confidence: 99%
“…Hakguder et al treated the fetus on 20 days of GA with intra-amniotic infusion of diuretic (furosemide) in order to lower the intra-amniotic meconium concentration and found decrease of intestinal serosa thickness. 99 Caporossi et al gave maternal supplementation with glutamine during the last 3 days of pregnancy but had no effect on the bowel. 100 Feng et al treated with afMSCs injected at the same creation of GS and found that this treatment mitigated the bowel damage potentially through a paracrine mechanism (TRASCET).…”
Section: Gastroschisis Model Surgically Created In Ratmentioning
confidence: 99%
“…peel). Воспалительным процессом кишечной стенки можно управлять, выполняя замену ам-ниотической жидкости или назначая фуросемид, который усиливает диурез у плода [23][24][25][26]. В нескольких исследова-ниях в этих условиях было выполнено заменное перелива-ние амниотической жидкости, однако позитивный эффект этой процедуры окончательно не доказан [24,27].…”
Section: гастрошизисunclassified